What are the global patterns of microplastic ingestion by fish? A scientometric review - Sacco, Vania Aparecida; Zuanazzi, Natana Raquel; Selinger, Amanda; Alliprandini da Costa, João Henrique [UNESP]; Spanhol Lemunie, Érika; Comelli, Camila Luiza; Abilhoa, Vinícius; Sousa, Fernando Carlos de; Fávaro, Luis Fernando; Rios Mendoza, Lorena M.; de Castilhos Ghisi, Nédia; Delariva, Rosilene Luciana (Elsevier, 2024)
The billions of tons of plastic released into the environment mostly fragment into smaller particles that reach rivers and oceans, posing toxicity risks to aquatic organisms. As fish serve as excellent environmental indicator organisms, this study aims to comprehensively review and quantify published data regarding the abundance of microplastics (MPs) ingested by fish through scientometric analysis. Systematic analysis reveals that global aquatic ecosystems are contaminated by MPs, with the characteristics of these contaminants stemming from inadequate disposal management practices. The abundance of MPs was recorded in several fish species, notably Cyprinus carpio in natural environments and Danio rerio in controlled environments. According to the surveyed studies, laboratory experiments do not accurately represent the conditions found in natural environments. The results suggest that, in natural environments, the predominant colors of MPs are blue, black, and red. Fibers emerged as the most prevalent type, with polyethylene (PE) and polypropylene (PP) being the most frequently identified chemical compositions. On the other hand, laboratory studies showed that the spheres and fragments ingested were predominantly polystyrene (PS) green, followed by the colors blue and red. This discrepancy complicates drawing accurate conclusions regarding the actual effects of plastic particles on aquatic biota. Given the enduring presence of plastic in the environment, it is imperative to consider and implement environmental monitoring for effective, long-term management.
Keywords: Aquatic organisms; Emerging pollutant; Fiber; Microplastics; Plastic particles